Meteorologic parameters and migraine headache: ED study - Yilmaz, Mustafa; Gurger, Mehtap; Atescelik, Metin; Yildiz, Mustafa; Gurbuz, Sukru (W B Saunders Co-Elsevier Inc, 2015)
Aim: Migraine is common in society and is one of the primary causes of chronic headache with episodes. In this study, we aimed to determine the role of meteorologic parameters and moon phase on triggering migraine attacks and effects on the number of patients presenting to the emergency department with migraine headaches. Materials and Methods: Patients admitted to the emergency department due to a migraine headache during a 1-year period were studied retrospectively. Correlation between moon phases, pressure, temperature, humidity, wind speed values of meteorologic observation, and recording station located in the same city and daily number of patients was analyzed. Results: A total of 3491 patients, of whom 72% (n = 2518) were women, were enrolled. The average daily number of patients was 9.6 +/- 4 (3-24). A statistically significant correlation was found between the number of daily patients and daily maximum temperature (P = .005), mean temperature (P = .013), minimum temperature (P = .041), and daily temperature change (P = .003). In addition, a negative correlation was found between the daily number of patients presenting to the emergency department and daily relative humidity (in percentage; P = .031). No significant relationship was found between moon phases and the number of patients. Conclusion: We have determined that the number of patients admitted to the emergency department with migraine headache has increased with high temperature and low humidity and that there is no relationship between the number of patients and moon phases. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Tension-Type Headache; Weather; Disability; Triggers